Student and Faculty Satisfaction with Their Dental Curriculum in a Dental College in Saudi Arabia - Maha Abdelsalam; Tobias E. Rodriguez; Lynn Brallier (Hindawi Limited, 2020)
The existing dental curriculum is taught at the College of Dentistry since 2002. The aim of this research is to explore the satisfaction levels of faculty members and students with that curriculum. This information will justify a curriculum reformation plan that addresses the aspirations of both faculty members and students. In this cross-sectional study, a two-section survey was prepared. Section 1 investigated the level of satisfaction with the curriculum, and Section 2 sought reasons why participants were satisfied with the curriculum. The questionnaire was electronically mailed to faculty members, interns, and senior students. Data were analyzed to identify patterns and points of disagreement expressed by faculty and students. The overall response rate was 68.7%. The mean standard deviation (SD) score in the study sample from all respondents was 5.0 (+3.0). Faculty significantly registered higher satisfaction than students (mean (SD) = 5.9 (+2.9) and 4.1 (+2.8), P=0.002). Results of multivariate analysis showed that faculty members were more satisfied with the curriculum than students because they thought the curriculum prepared competent graduates (regression coefficient = 1.76 and 0.69). Teaching staff and students' satisfaction levels with the curriculum were significantly associated with their perception that the curriculum produces competent graduates. Areas with low students' satisfaction levels were related to promotion of engagement with others and development of critical thinking and problem-solving skills. These areas should be the focus of future curriculum reformation to prepare competitive graduates with competences aligned with the recommendations of the Saudi Arabia Qualification Framework and of the international benchmarks.